Work-Related Musculoskeletal Discomfort and Injury in Craniofacial and Maxillofacial Surgeons. Issue 7 (October 2019) - Howarth, Ashley L.; Hallbeck, M. Susan; Lemaine, Valerie; Singh, Davinder J.; Noland, Shelley S.
Abstract : Introduction: Long, complex surgical procedures with non-ergonomic postures, headlights, loupe magnification, and microscope use may put craniofacial and maxillofacial surgeons at an increased risk of work-related musculoskeletal discomfort (WRMD). Identifying the prevalence and impact of WRMD may guide preventive strategies to prolong well-being, job satisfaction, and career duration. Methods: A 31-question survey was designed to evaluate WRMD. The survey was sent to American Society of Craniofacial Surgeons and American Society of Maxillofacial Surgeons members. The survey was created and distributed electronically through a private survey research center (Qualtrics Survey Software). Results: There were 95 respondents (23.75% response rate): 75% male, 56% aged 31 to 50 years old, and 73% in academic practice. On a scale of 0 to 10 (0 no pain, 10 worst pain), WRMD for surgery without loupes/microscope had a median of 3, with loupes 4, and with microscope 5. Pain was most common in the neck. Pain within 4 hours of surgery was present in 55% and 38% feared pain would influence future surgical performance. Surgeon discomfort affects posture (72%), stamina (32%), sleep (28%), surgical speed (24%), relationships (18%), and concentration (17%). Medical treatment for discomfort was sought by 22%. Time off work for treatment occurred in 9%. Conclusion: The WRMD can affect many aspects of a craniofacial or maxillofacial surgeon's life and has the potential to shorten or end a career. Occupational health and surgical ergonomics should be emphasized during surgical training and in surgical practice. Abstract : Supplemental Digital Content is available in the text